Sola Experientia: Suatu Analisis Terhadap Teologi Schleiermacher - Marde Christian Stenly Mawikere (Sekolah Tinggi Teologi Simpson, 2019)
This article is an overview of the theology of Friedrich Schleiermacher, known as the Father of Modern Theology. By using qualitative research methods on various available literature that review the life and theological thinking of Schleiermacher, the author tries to reveal that the unique thinking of FriedrichSchleiermacher's theology is strongly influenced by his spiritual background, parental influence, church origin and tradition, educational patterns and the thought of his theological education and zeit geist (the spirit of the times) who were carrying the current of modern thought when Schleiermacher lived. On the one hand, Schleiermacher's theology is often considered to be liberal in the theological paradigm of reform and evangelicalism because it departs from feeling, not from the spirit of Sola Scriptura. But on the other hand, Schleiermacher's theology makes a positive contribution because it gives a place to the experience of faith (Sola Experientia) with a living God who can not only be reached with philosophia or wisdom. Artikel ini merupakan Tinjauan terhadap Teologi dari Friedrich Schleiermacher, yang dikenal sebagai Bapak Teologi Moderen.Dengan menggunakan metode penelitian kualitatif terhadap berbagai literatur yang telah tersedia yang mengulas mengenai kehidupan dan pemikiran teologi dari Schleiermacher, maka penulis mencoba untuk mengungkapkan bahwa keunikan pemikiran Teologi FriedrichSchleiermacher sangat dipengaruhi oleh latar belakang kehidupan rohaninya, pengaruh orangtua, asal dan tradisi gereja, pola pendidikan dan pemikiran pendidikan teologinya serta zeit geist (semangat zaman) yang sedang membawa arus pemikiran moderen pada waktu Schleiermacher hidup. Pada satu sisi, Teologi Schleiermacher kerap dianggap liberal dalam paradigma teologi reformasi dan evangelical karena ia berangkat darifeeling, bukan dari semangat Sola Scriptura. Namun pada sisi lain, Teologi Schleiermacher memberikan kontribusi positif sebab memberikan tempat kepada pengalaman iman (Sola Experientia) dengan Allah yang hidup yang tidak hanya dapat dijangkau dengan philosophia atau wisdom.